Hubungan Antara Volume Prostat dan IPSS Score pada Pasien BPH di Rumah Sakit Siti Khodijah Muhammadiyah Cabang Sepanjang - Waskita, Shakina Reza; Putra, Muslim Andala; Mochtar, Nur Mujadiddah; Himawan, Budi (Faculty of Medicine, Universitas Andalas, 2024)
Benign Prostatic Hyperplasia (BPH) is the growth of non-malignant cells or hyperplasia of prostate tissue, which causes Lower Urinary Tract Symptoms (LUTS) in men. One guide to direct and determine the symptoms of obstruction due to prostate enlargement is the International Prostate Symptom Score (IPSS). Objective: To determined the relationship between prostate volume and IPSS score in BPH patients at Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital. Methods: This was an analytic observational study using a prospective cohort method. The sample selection used consecutive sampling techniques in accordance with predetermined inclusion and exclusion criteria for collecting data using primary and secondary data, abdominal ultrasound data, and the IPSS questionnaire. The number of samples used was 30 patients from November 2022 to April 2023. Results: The prostate volume in grade II was 46.7%, while for grade I and grade III were 33.3% and 20%, respectively. For the results of the IPSS, the moderate category was 76.7%, with mild and severe IPSS scores at 10% and 13.3%, respectively. The Spearman test results showed that the p-value was 0.006 <0.05, the value of r = 0.486, and the correlation coefficient was positive, meaning there was a unidirectional relationship between prostate volume and the IPSS score. Conclusion: There is a reasonably strong relationship between prostate volume and IPSS score in BPH patients at Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital.Keywords: Â BPH, prostate volume, IPSS